Preparation method of electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surface

The preparation of nickel-sulfur-phosphorus amorphous coatings by electroplating process solves the problems of low efficiency and poor surface roughness of electroless nickel-phosphorus amorphous coatings in ultra-precision machining, and realizes efficient and low-hardness amorphous coating processing to meet the surface precision requirements of high-end products.

CN120888995APending Publication Date: 2025-11-04SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511068561.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing electroless nickel-phosphorus amorphous coatings suffer from problems such as porosity affecting surface roughness and low preparation efficiency in ultra-precision machining, and long-term machining leads to severe tool wear.

Method used

A nickel-sulfur-phosphorus amorphous coating was prepared by electroplating. By controlling the composition and parameters of the electrolyte, including the concentration and pH value of nickel salts, sodium thiosulfate, thiourea, and phosphate salts, and combining it with a constant current pulse electroplating method, a low-hardness amorphous coating was prepared.

Benefits of technology

It significantly improves the coating preparation efficiency, reduces tool wear, and the surface roughness after ultra-precision machining is lower than that of electroless nickel-phosphorus amorphous coating, meeting the requirements for the use of high-performance metal materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120888995A_ABST
    Figure CN120888995A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an electroplated nickel-based amorphous polishing coating for ultra-precision machining of a metal surface. According to the method, a constant-current power supply is adopted for electroplating a metal sample, the metal sample serves as a cathode, and the electroplated nickel-based amorphous polishing coating is obtained; electrolyte for electroplating comprises nickel salt, sodium thiosulfate, thiourea, phosphorus salt, auxiliary salt, a buffering agent, a surfactant and an additive. According to the method, the sodium thiosulfate is used for partially replacing thiourea, concentration adaptation of the sulfur salt and the phosphorus salt is combined, the amorphous coating free of microdefects is prepared, electroplating parameters are optimally matched, and the amorphous coating with evenly distributed components and hardness can be obtained. According to the nickel-sulfur-phosphorus amorphous coating electroplated on the metal surface, the cutting rate of machining on a polishing coating is increased, and meanwhile, the preparation efficiency of the nickel-sulfur-phosphorus amorphous coating electroplated on the metal surface is remarkably higher than that of a chemical nickel-phosphorus amorphous coating; the electroplated nickel-sulfur-phosphorus amorphous coating can be used as a polishing coating with extremely low surface roughness obtained by ultra-precision machining of a metal surface.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of forming extremely low surface roughness on metal surface by ultra-precision machining, and particularly relates to a preparation method of electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surface. BACKGROUND

[0002] Metal materials are gradually becoming a reliable choice for preparing ultra-precision surfaces due to their good machinability, relatively low density and excellent thermal conductivity. With the development and progress of science and technology, various high-performance optical, optoelectronic and semiconductor products are emerging, and higher requirements are put forward for the surface precision of metal materials used in products. For example, high-performance reflective optical systems have great application prospects in the fields of optical reflectors, collection lenses, detectors and projection arrays. The high resolution and high precision of optical systems require mirrors to have extremely low surface roughness, thereby putting forward strict requirements on mirror manufacturing materials to ensure the superior performance of optical mirrors. The development of ultra-precision machining technology has rapidly improved the surface precision of metal materials. However, when the grain size is used as the machining scale, the plastic deformation of polycrystalline metal materials during ultra-precision machining shows anisotropy, and the defects (such as dislocations, grain boundaries, cracks and pores) in the polycrystalline metal materials also cause local abnormal deformation fluctuations. The surface quality of metal materials after ultra-precision machining is still difficult to meet the use requirements of high-end products.

[0003] Currently, electroless plating of nickel-phosphorus amorphous coating is used as a polishing layer for ultra-precision machining of metal materials in industry, which can effectively improve the surface precision of metal materials after ultra-precision machining. The coating has good processing performance, suitable amorphous structure and mechanical properties. Research results show that the surface roughness of aluminum mirrors after ultra-precision machining can reach the nanometer level. However, the Ni-P coating prepared by electroless plating is prone to form small-scale pores due to the escape of a large amount of hydrogen gas during the autocatalytic process, which seriously affects the surface roughness after ultra-precision machining. Therefore, the growth rate of the electroless plated coating must be controlled below 5 μm / h to reduce the influence of pores on the surface roughness of metal materials after ultra-precision machining, thereby prolonging the preparation process of electroless plating nickel to several days to meet the thickness requirement (e.g. > 200 μm) of the polishing layer for ultra-precision machining process. The long preparation process inevitably faces many uncontrollable factors affecting the quality of Ni-P amorphous coating, and the preparation efficiency of the entire process is extremely low. In addition, the Vickers microhardness of amorphous Ni-P coating is as high as about 650 HV0.05, which adversely affects the tool wear during long-time ultra-precision machining. Therefore, there is an urgent need to develop a new process for efficiently preparing an amorphous polishing layer with lower hardness.

[0004] Based on the applicability of the Ni-P amorphous polishing coating in the ultra-precision machining of aluminum reflectors, it can be reasonably inferred that the nickel-based amorphous coating is suitable for being used as a polishing layer for ultra-precision machining of metal materials due to its unique microstructure and mechanical properties. Therefore, the nickel-based amorphous coating prepared by the electroplating method which has higher preparation efficiency can be considered. The electroplating process has been widely used in the preparation of nickel-based alloy coatings, and the growth rate of the coating is fast. In the field of metal surface treatment, the electroplating process also occupies a large market share. Therefore, it is feasible to prepare the nickel-based amorphous polishing coating on the metal surface by electroplating. The nickel-based amorphous coating prepared by electroplating mainly includes Ni-P and Ni-S alloys. Compared with the Ni-P coating, the Ni-S coating has comparable mechanical properties. In addition, the hardness of the Ni-S coating is lower than that of the Ni-P coating, which is beneficial to the rapid cutting of the polishing layer and the reduction of the wear of the diamond tool during the ultra-precision machining process. Therefore, the electroplated Ni-S-P or Ni-S amorphous coating is a potential material for replacing the electroless plated Ni-P amorphous coating as the polishing layer of the aluminum reflector.

[0005] Based on the above status and design ideas, the application provides a preparation method of an electroplated nickel-based amorphous polishing layer for ultra-precision machining of a metal surface. The method is used for preparing the Ni-S-P amorphous coating on the metal surface by the electroplating process. The composition and concentration of the electrolyte can be adjusted to prepare the Ni-S-P amorphous coating with different component contents and hardness. The microhardness of the coating is lower than that of the electroless plated Ni-P amorphous coating. After the ultra-precision machining by the single-point diamond turning and the magnetorheological grinding and polishing, the surface roughness of the coating is lower than that of the electroless plated Ni-P amorphous coating. The application provides a new method for preparing the nickel-based amorphous polishing layer for the ultra-precision machining of the metal surface with high surface precision. The Ni-S-P amorphous coating can be used as the polishing layer for the ultra-precision machining of the metal surface. SUMMARY

[0006] The application aims to provide a preparation method of an electroplated nickel-based amorphous polishing coating for ultra-precision machining of a metal surface to solve the problems in the prior art. The method is used for preparing the nickel-based amorphous coating on the metal surface by the electroplating method. The surface roughness of the nickel-sulfur-phosphorus amorphous coating after the ultra-precision machining and polishing is extremely low. The coating has better ultra-precision machining and polishing performance than the electroless plated nickel-phosphorus amorphous coating.

[0007] The object of the application can be achieved by the following scheme:

[0008] The application provides a preparation method of an electroplated nickel-based amorphous polishing coating for ultra-precision machining of a metal surface, which comprises the following steps:

[0009] The metal sample is used as the cathode to perform electroplating by using a constant current power supply, so that the electroplated nickel-based amorphous polishing coating is obtained.

[0010] The electrolyte used for electroplating includes nickel salt, sodium thiosulfate, thiourea, phosphorus salt, auxiliary salt, buffer, surfactant, additive.

[0011] As an embodiment of the present application, the concentration of the nickel salt in the electrolyte is 20-100 g / L. The nickel salt includes one or more of nickel sulfate or its hydrate, nickel chloride or its hydrate.

[0012] As an embodiment of the present application, the concentration of the sodium thiosulfate in the electrolyte is 10-25 g / L, and the concentration of the thiourea is 10-25 g / L. The combination of the thiourea and the sodium thiosulfate in the present application is beneficial to promote the entry of S into the plating layer. The concentration of the sodium thiosulfate can be 10-20 g / L, 15-25 g / L, 18-22 g / L, and the concentration of the thiourea can be 10-20 g / L, 15-25 g / L, 13-17 g / L.

[0013] As an embodiment of the present application, the mass ratio of the sodium thiosulfate to the thiourea in the electrolyte is preferably 0.5-1.5:1; more preferably 0.6-1.25:1.

[0014] As an embodiment of the present application, the concentration of the phosphorus salt in the electrolyte is 0-50 g / L, preferably 30-40 g / L. The phosphorus salt includes one or more of sodium hypophosphite or its hydrate.

[0015] As an embodiment of the present application, the concentration of the auxiliary salt in the electrolyte is 20-40 g / L. The auxiliary salt includes one or more of sodium citrate, ammonium hydrogen fluoride, ammonium sulfate.

[0016] As an embodiment of the present application, the concentration of the buffer in the electrolyte is 20-40 g / L. The buffer includes one or more of boric acid, citric acid.

[0017] As an embodiment of the present application, the concentration of the surfactant in the electrolyte is 0.1-1 g / L. The surfactant includes one or more of sodium dodecyl benzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate.

[0018] As an embodiment of the present application, the concentration of the additive in the electrolyte is 0.1-0.6 g / L. The additive includes one or more of saccharin, sodium polydithiobis propane sulfonate, coumarin, polyethylene glycol, ytterbium chloride, ytterbium nitrate, m-diphenol.

[0019] As an embodiment of the present application, the pH of the electrolyte is controlled in the range of 3-6, preferably in the range of 3.5-5.0. The pH of the solution prepared by the present application is adjusted by potassium hydroxide and sulfuric acid

[0020] As an embodiment of the present application, the preparation of the electrolyte: the nickel salt, sodium thiosulfate, thiourea, phosphorus salt, auxiliary salt, buffer are dissolved in pure water respectively, then the nickel salt solution, sulfur salt solution, phosphorus salt solution, auxiliary salt solution and buffer solution are mixed uniformly in turn, then the surfactant and additive are added and mixed uniformly, finally the pH value of the solution is adjusted with potassium hydroxide and sulfuric acid.

[0021] As an embodiment of the present application, the electroplating is carried out in a constant current pulse output mode. During the electroplating, the duty cycle of the pulse is between 10-70%, the frequency of the pulse is between 100-50000Hz, the current density range is between 0.1-4A / dm 2 , the water bath temperature of the electrolyte is 20-50℃, the stirring speed of the electrolyte is 10-400rpm, and the electroplating time is 1-12h. Preferably, the duty cycle of the pulse is between 30-50%, the frequency of the pulse is between 200-10000Hz, the current density range is between 0.5-2A / dm 2 , the water bath temperature of the electrolyte is 30-40℃, the stirring speed of the electrolyte is 30-150rpm, and the electroplating time is 2-8h. More preferably, the duty cycle of the pulse is between 45-50%, the frequency of the pulse is between 500-1000Hz, the current density range is between 1-1.5A / dm 2 , the water bath temperature of the electrolyte is 35-40℃, the stirring speed of the electrolyte is 30-50rpm, and the electroplating time is 5-6h.

[0022] As an embodiment of the present application, the material of the metal sample includes one of aluminum, aluminum alloy, silver, gold, steel, nickel, nickel alloy, copper, and copper alloy.

[0023] As an embodiment of the present application, the metal sample is pretreated, alkali washed, acid washed, and zinc immersed before electroplating.

[0024] Preferably, the pretreatment is to polish, polish and ultrasonic clean the metal sample with sandpaper, so as to sufficiently remove the surface organic matter and oxide layer. The sandpaper polishing is to polish the metal sample with SiC water-resistant sandpaper of 180#, 400#, 800#, 1500# and 3000# in turn, then polish with diamond polishing liquid of 9μm, 3μm and 1μm particle size for 5min in turn, and then ultrasonic clean in acetone, pure water and ethanol for 5min in turn to remove the pollutants on the surface of the metal sample.

[0025] Preferably, the alkali cleaning solution has a component concentration formula of 2-5 g / L of NaOH, 40-60 g / L of Na2CO3, 40-60 g / L of Na3PO4, 0.5-1 g / L of sodium dodecyl sulfate or sodium dodecyl benzene sulfonate, the alkali cleaning treatment temperature is 85-90°C, and the alkali cleaning treatment time is 5-10 min.

[0026] Preferably, the material of the metal sample is one of aluminum, aluminum alloy, silver, gold, steel, nickel, and nickel alloy.

[0027] The acid cleaning solution for aluminum and aluminum alloy has a component concentration formula of 5-10 wt.% of HNO3, 70-80 g / L of NH4HF2, and 10-15 wt.% of H2SO4, and is treated at room temperature for 60-80 s;

[0028] The acid cleaning solution for silver and gold has a formula of 15-20 wt.% of HNO3 and 45-60 wt.% of HCl, and is treated at room temperature for 3-4 min;

[0029] The acid cleaning solution for steel has a formula of 150-230 g / L of H2SO4 and 250-300 g / L of HCl, and is treated at 40-50°C for 20-40 s;

[0030] The acid cleaning solution for nickel and nickel alloy has a formula of 15-20 mL / L of H3PO4 and 15-45 mL / L of HNO3, and is treated at room temperature for 3-4 min.

[0031] Preferably, the zinc immersion solution has a component concentration formula of 200-300 g / L of NaOH, 40-60 g / L of ZnO, 1-3 g / L of FeCl3, and 5-10 g / L of NaKC4H4O6, and is treated at room temperature for 5-10 min.

[0032] Compared with the prior art, the present application has the following beneficial effects:

[0033] (1) The time for preparing the nickel-based amorphous polishing coating in the electroplating mode is significantly less than that in the chemical plating Ni-P amorphous coating, and the preparation efficiency of the coating is significantly improved.

[0034] (2) The hardness of the electroplated nickel-based amorphous coating is lower than that of the chemical plating Ni-P amorphous coating, which is beneficial to reducing the wear of machining tools and improving the machining and cutting efficiency of the coating.

[0035] (3) The surface roughness of the electroplated nickel-based amorphous coating after ultra-precision machining reaches a level comparable to that of the chemical plating Ni-P amorphous coating, and the component of the amorphous coating can be optimized by adjusting the electrolyte formula, so that the surface roughness after ultra-precision machining is lower than that of the chemical plating Ni-P amorphous coating, and the use demand of high-performance metal materials can be met. BRIEF DESCRIPTION OF DRAWINGS

[0036] Other features, objects, and advantages of the present application will become more apparent from the following detailed description of non-limiting embodiments thereof, when read in conjunction with the accompanying drawings:

[0037] Figure 1 Micrograph of (a) electroplated Ni-S-P amorphous coating, (b) surface roughness after superfinishing, (c) cross-sectional hardness distribution with coating thickness, and (d) XRD phase structure of Example 1;

[0038] Figure 2 Micrograph of (a) electroplated Ni-S amorphous coating, (b) surface roughness after superfinishing, (c) cross-sectional hardness distribution with coating thickness, and (d) XRD phase structure of Example 2;

[0039] Figure 3 Micrograph of electroplated Ni-S-P amorphous coating of Example 3;

[0040] Figure 4 Micrograph of electroplated Ni-S amorphous coating of Example 4;

[0041] Figure 5 Micrograph of (a) electroplated Ni-P amorphous coating, (b) surface roughness after superfinishing, (c) cross-sectional hardness distribution with coating thickness, and (d) XRD phase structure of Comparative Example 1;

[0042] Figure 6 Atomic force microscope (AFM) micrograph and surface roughness of (a, c) Example 2 and (b, d) Comparative Example 1 after single-point diamond turning (a, b) and magnetorheological finishing (c, d);

[0043] Figure 7 Micrograph of surface of Comparative Example 2 after single-point diamond turning (a) and magnetorheological finishing (b)

[0044] Figure 8 Micrograph of electroplated Ni-S-P coating of Comparative Example 3;

[0045] Figure 9 Micrograph of electroplated Ni-S coating of Comparative Example 4;

[0046] Figure 10 Micrograph of electroplated Ni-S coating of Comparative Example 5;

[0047] Figure 11 Micrograph of electroplated Ni-S-P coating of Comparative Example 6;

[0048] Figure 12Surface micrograph of the electroplated Ni-S-P coating of Comparative Example 7;

[0049] Figure 13 Surface micrograph of the electroplated Ni-S-P coating of Comparative Example 8. DETAILED DESCRIPTION

[0050] The application will be described in detail below with specific embodiments. The following examples will help those skilled in the art to further understand the application, but do not limit the application in any form. It should be noted that for those skilled in the art, without departing from the concept of the application, a number of modifications and improvements can be made, which are within the scope of the application.

[0051] Example 1

[0052] The present embodiment provides a preparation method of electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surface, comprising the following steps:

[0053] The aluminum-silicon alloy sample (42wt.% Si) was polished on the metal sample with 180#, 400#, 800#, 1500# and 3000# SiC water-resistant sandpaper, and then polished with diamond polishing liquid with particle sizes of 9 μm, 3 μm and 1 μm for 5 min, respectively. After polishing, the metal sample was ultrasonically cleaned in acetone, pure water and ethanol for 5 min, respectively, to remove the pollutants on the surface of the metal sample.

[0054] The aluminum-silicon alloy was immersed in an alkaline cleaning solution containing 2 g / L NaOH, 40 g / L Na2CO3, 40 g / L Na3PO4 and 0.5 g / L sodium dodecyl sulfate for 8 min, and the water bath temperature was 85°C, and then rinsed with pure water.

[0055] The aluminum-silicon alloy was immersed in an acid cleaning solution containing 5wt.% HNO3, 80 g / L NH4HF2 and 10wt.% H2SO4 at room temperature for 60 s, and then rinsed with pure water.

[0056] The aluminum-silicon alloy was immersed in a zinc immersion solution containing 200 g / L NaOH, 50 g / L ZnO, 1 g / L FeCl3 and 5 g / L NaKC4H4O6 at room temperature for 5 min, and then rinsed with pure water.

[0057] The electroplating was carried out in a constant current pulse output mode, the duty cycle of the pulse was set to 50%, the frequency of the pulse was 1000 Hz, the current density was 1.5 A / dm 2 , the water bath temperature of the electrolyte was 40°C, the stirring speed of the electrolyte was 50 rpm, the aluminum-silicon alloy was used as the cathode, the pure nickel plate was used as the anode, and the electroplating time was 6 h.

[0058] The concentration formula of the electrolyte for preparing the Ni-S-P amorphous coating is 50 g / L of nickel sulfate, 10 g / L of nickel chloride, 20 g / L of thiourea, 15 g / L of sodium thiosulfate, 35 g / L of sodium hypophosphite, 40 g / L of sodium citrate, 20 g / L of boric acid, 0.1 g / L of sodium dodecyl sulfate, 0.2 g / L of saccharin, and 0.2 g / L of ytterbium chloride, and the pH of the solution is adjusted to about 4.0.

[0059] The electroplated aluminum-silicon alloy is subjected to single-point diamond turning and magnetorheological finishing super-precision machining, and the surface roughness is analyzed by using a white light interferometer and an atomic force microscope.

[0060] Figure 1 The results show that the Ni-S-P coating is completely amorphous, the average micro-Vickers hardness is 535 HV0.05, the surface microstructure is in the form of convex bumps with a size of about 20 μm, and there are obvious grooves between the convex bumps, but no obvious cracks and pores are generated. After super-precision machining, the surface roughness Sa and Sq are 0.468 nm and 0.806 nm respectively, which reaches the range of 1 nm precision. The polishing performance of the Ni-S-P amorphous coating is excellent.

[0061] Example 2

[0062] The embodiment provides a preparation method of an electroplated nickel-based amorphous polishing coating for super-precision machining of a metal surface, which comprises the following steps:

[0063] The 40Cr alloy steel sample is polished by using SiC water-resistant sandpapers with grits of 180#, 400#, 800#, 1500# and 3000# in sequence, and then polished by using diamond polishing liquids with particle sizes of 9 μm, 3 μm and 1 μm in sequence for 5 min. After polishing, the metal sample is ultrasonically cleaned in acetone, pure water and ethanol in sequence for 5 min to remove pollutants on the surface of the metal sample.

[0064] The 40Cr alloy steel is immersed in an alkaline cleaning solution containing 5 g / L of NaOH, 50 g / L of Na2CO3, 50 g / L of Na3PO4 and 0.5 g / L of sodium dodecyl sulfate for 5 min, and the water bath temperature is 85 ℃, and then the 40Cr alloy steel is washed with pure water.

[0065] The 40Cr alloy steel is immersed in an acid cleaning solution containing 150 g / L of H2SO4 and 300 g / L of HCl at 50 ℃ for 60 s, and then washed with pure water.

[0066] The 40Cr alloy steel is immersed in a zinc immersion solution containing 200 g / L of NaOH, 50 g / L of ZnO, 1 g / L of FeCl3 and 5 g / L of NaKC4H4O6 at room temperature for 5 min, and then washed with pure water.

[0067] The electroplating is performed in a constant current pulse output mode, the duty cycle of the pulse is set to 50%, the frequency of the pulse is 500 Hz, the current density is 1 A / dm 2 , the water bath temperature of the electrolyte is 40°C, the stirring speed of the electrolyte is 30 rpm, 40Cr alloy steel is used as the cathode, pure nickel plate is used as the anode, and the electroplating time is 5 h.

[0068] The component concentration formula of the electrolyte for preparing the Ni-S-P amorphous coating is 50 g / L of nickel sulfate, 10 g / L of thiourea, 10 g / L of sodium thiosulfate, 20 g / L of ammonium sulfate, 20 g / L of sodium citrate, 0.1 g / L of sodium dodecyl benzene sulfonate, 0.2 g / L of saccharin, 0.2 g / L of coumarin, and 0.2 g / L of polyethylene glycol, and the pH of the solution is adjusted to about 5.0.

[0069] The electroplated 40Cr alloy steel is subjected to single-point diamond turning and magnetorheological finishing ultra-precision machining, and the surface roughness is analyzed by using a white light interferometer and an atomic force microscope.

[0070] Figure 2 It is shown in the table that the Ni-S coating is a complete amorphous structure, the average micro Vickers hardness is 406 HV0.05, the hardness is lower than that of the Ni-S-P amorphous coating, the surface microstructure is in the form of convexes with a size of about 10 μm, there are obvious grooves between the convexes, but no obvious cracks and holes are generated, and the surface roughness Sa and Sq are 0.668 nm and 0.834 nm respectively after ultra-precision machining, the surface roughness is slightly higher than that of the Ni-S-P amorphous coating, but still reaches the range of 1 nm precision, and the Ni-S amorphous coating still has excellent polishing performance. On the other hand, the amorphous coating system co-doped with S and P has a slightly increased micro hardness, but is more conducive to obtaining an amorphous coating with better ultra-precision machining performance.

[0071] Example 3

[0072] In this example, the Ni-S-P amorphous coating is electroplated on the surface of an aluminum-silicon alloy (42 wt.% Si), and all the preparation processes are the same as those in Example 1, except for the components of the electroplating solution. The difference between the electroplating solution of Example 3 and that of Example 1 is that the sulfur salts are configured as 20 g / L of thiourea and 25 g / L of sodium thiosulfate.

[0073] Figure 3 The surface microstructure of Example 3 is shown in the table, the coating surface presents a uniform convex structure, the size of the convexes is about 10 μm, the convex structures are uniformly distributed on the surface, and there are no other cracks or hole defects except the boundaries between the convexes.

[0074] Example 4

[0075] The embodiment electroplated Ni-S amorphous coating on the surface of 40Cr alloy steel. Except for the composition of the electroplating solution, all the preparation processes were the same as those of Example 2. The difference between the electroplating solution of Example 4 and that of Example 2 was that the concentration of sodium thiosulfate was 5 g / L.

[0076] Figure 4 The surface micro-morphology of Example 4 can be seen from which it can be seen that a complete coating can be electroplated, the coating surface contains convexes of different diameters, the surface uniformity is lower than that of Example 2, and the roughness is higher, indicating that appropriate concentration of sodium thiosulfate can prepare a Ni-S amorphous coating with better surface properties.

[0077] Comparative Example 1

[0078] The present comparative example is chemical plating of Ni-P amorphous coating on the surface of aluminum-silicon alloy (42 wt.% Si). The Ni-P amorphous coating was prepared on the surface of the pretreated aluminum-silicon alloy using a commonly used chemical plating nickel solution, including the following steps:

[0079] The aluminum-silicon alloy sample (42 wt.% Si) was polished using 180#, 400#, 800#, 1500# and 3000# SiC water-resistant sandpaper in sequence, and then polished using diamond polishing liquid with particle sizes of 9 μm, 3 μm and 1 μm in sequence for 5 min. After polishing, the sample was ultrasonically cleaned in acetone, pure water and ethanol in sequence for 5 min to remove contaminants on the surface of the metal sample.

[0080] The aluminum-silicon alloy was immersed in an alkali cleaning solution containing 2 g / L NaOH, 40 g / L Na2CO3, 40 g / L Na3PO4 and 0.5 g / L sodium dodecyl sulfate for 8 min at a water bath temperature of 85°C, and then rinsed with pure water.

[0081] The aluminum-silicon alloy was immersed in an acid cleaning solution containing 5 wt.% HNO3, 80 g / L NH4HF2 and 10 wt.% H2SO4 at room temperature for 60 s, and then rinsed with pure water.

[0082] The aluminum-silicon alloy was immersed in a zinc immersion solution containing 200 g / L NaOH, 50 g / L ZnO, 1 g / L FeCl3 and 5 g / L NaKC4H4O6 at room temperature for 5 min, and then rinsed with pure water.

[0083] The composition of the solution for preparing the chemical plating Ni-P amorphous coating was 30 g / L nickel sulfate, 20 g / L sodium hypophosphite, 20 g / L boric acid, 10 g / L lactic acid and 0.1 g / L polyethylene glycol. The pH of the solution was adjusted to about 4.6, the water bath temperature was 86°C, and the chemical plating time was 24 h.

[0084] The electroless plated aluminum-silicon alloy was ultra-precisely machined by single-point diamond turning and magnetorheological finishing, and the surface roughness was analyzed by white light interferometer and atomic force microscope.

[0085] The electroless plated Ni-P amorphous coating is a currently used polishing coating for ultra-precise machining of metal material surface, and the electroless plated Ni-P amorphous coating has a micro-Vickers hardness of 620 HV0.05, which is obviously higher than that of the electroplated Ni-S and Ni-S-P amorphous coatings. Figure 5 It can be seen from Table 1 that the electroless plated Ni-P coating of Comparative Example 1 is an amorphous coating, and the average micro-Vickers hardness is 620 HV0.05, which is obviously higher than that of the electroplated Ni-S and Ni-S-P amorphous coatings. After ultra-precise machining, the surface roughness Sa and Sq of the electroless plated Ni-P coating are 1.083 nm and 1.361 nm, respectively, which does not reach the surface precision within 1 nm, and is obviously higher than the surface roughness of the coatings of Example 1 and Example 2, indicating that the electroplated nickel-based Ni-S-P amorphous coating has a better ultra-precise machining performance than the currently used electroless plated Ni-P amorphous coating, and is expected to replace the existing electroless plated Ni-P amorphous coating as a polishing coating for ultra-precise machining of metal material.

[0086] The surface roughness of Example 2 and Comparative Example 1 was further analyzed by AFM. Figure 6 It can be seen from Table 2 that after single-point diamond ultra-precise machining, the Sq of the electroplated Ni-S amorphous coating (1.36 nm) is lower than that of the electroless plated Ni-P amorphous coating (1.99 nm), and the surface roughness Sq of the coating is reduced after magnetorheological grinding and polishing. The tool marks of the single-point diamond machining disappear, and the Sq of the electroplated Ni-S amorphous coating is 0.714 nm, reaching the range of 1 nm, while the Sq of the electroless plated Ni-P amorphous coating (1.24 nm) is still higher than 1 nm, again proving that the electroplated Ni-S amorphous coating has a better ultra-precise machining performance than the electroless plated Ni-P amorphous coating.

[0087] Comparative Example 2

[0088] This comparative example is to electroplate a Ni-S-P amorphous coating on the surface of an aluminum-silicon alloy (42 wt.% Si). Except for the composition of the electroplating solution, all the preparation processes are the same as those of Example 1. The difference between Comparative Example 2 and Example 1 is that the sulfur salt is completely replaced by 35 g / L thiourea instead of the combination of 20 g / L thiourea and 15 g / L sodium thiosulfate. The specific composition concentration formula of the electrolyte used for preparing the Ni-S-P amorphous coating is 50 g / L nickel sulfate, 10 g / L nickel chloride, 35 g / L thiourea, 35 g / L sodium hypophosphite, 40 g / L sodium citrate, 20 g / L boric acid, 0.1 g / L sodium dodecyl sulfate, 0.2 g / L saccharin, and 0.2 g / L ytterbium chloride, and the pH of the solution is adjusted to about 4.0.

[0089] Figure 7The surface morphology of the Ni-S-P amorphous coating prepared for Comparative Example 2 can be seen from which, when only thiourea is used as a sulfur salt, the coating has a large number of obvious defects after super-precision machining, indicating that the use of sodium thiosulfate to replace part of the thiourea is conducive to the uniform and defect-free growth of the coating, and the S provided by the sodium thiosulfate significantly improves the super-precision machining of the coating.

[0090] Comparative Example 3

[0091] This comparative example is to electroplate a Ni-S-P amorphous coating on the surface of an aluminum-silicon alloy (42 wt.% Si), and all the preparation processes are the same as those of Example 1, except for the composition of the electroplating solution. The difference between Comparative Example 3 and Example 1 is that the concentration of the phosphorus salt is adjusted to 80 g / L of sodium hypophosphite. The specific composition concentration formula of the electrolyte used to prepare the Ni-S-P amorphous coating is 50 g / L of nickel sulfate, 10 g / L of nickel chloride, 20 g / L of thiourea, 15 g / L of sodium thiosulfate, 80 g / L of sodium hypophosphite, 40 g / L of sodium citrate, 20 g / L of boric acid, 0.1 g / L of sodium dodecyl sulfate, 0.2 g / L of saccharin, and 0.2 g / L of ytterbium chloride. The pH of the solution is adjusted to be around 4.0.

[0092] Figure 8 The surface morphology of the Ni-S-P amorphous coating prepared for Comparative Example 3 can be seen from which, when the concentration of sodium hypophosphite is too high, the coating shows a large number of holes, indicating that the concentration of sodium hypophosphite providing the phosphorus source needs to be adjusted appropriately to prepare a coating without obvious defects, and the concentrations of the sulfur source and the phosphorus source need to be adapted.

[0093] Comparative Example 4

[0094] This comparative example is to electroplate a Ni-S amorphous coating on the surface of a 40Cr alloy steel, and all the preparation processes are the same as those of Example 2, except for the current density. The difference between Comparative Example 4 and Example 2 is that the current density is increased from 1 A / dm 2 to 2.5 A / dm 2 . The specific electroplating parameters used to prepare the Ni-S amorphous coating are as follows: constant current pulse output mode is used for electroplating, the duty cycle of the pulse is set to 50%, the frequency of the pulse is 500 Hz, the current density is 2.5 A / dm 2 , the water bath temperature of the electrolyte is 40°C, the stirring speed of the electrolyte is 30 rpm, the 40Cr alloy steel is used as the cathode, and a pure nickel plate is used as the anode. The electroplating time is 5 h.

[0095] Figure 9 The surface micro-morphology of the Ni-S coating prepared for Comparative Example 4 can be seen from which, when the current density is 2.5 A / dm 2The prepared Ni-S coating of Comparative Example 5 shows a large number of hole defects, and a large number of spherical nanoparticles are generated on the surface. The high current density in the electroplating process is not conducive to the formation of a defect-free coating.

[0096] Comparative Example 5

[0097] This comparative example is to electroplate a Ni-S amorphous coating on the surface of a 40Cr alloy steel. Except for the composition of the electroplating solution, all the preparation processes are the same as those of Example 2. The difference between the electroplating solution of Comparative Example 5 and Example 2 is that the sulfur salt is configured as 10 g / L thiocarbamide and 20 g / L sodium thiosulfate.

[0098] Figure 10 The surface micro-morphology of the prepared Ni-S coating of Comparative Example 5 can be seen from which the Ni-S coating prepared by the sulfur salt configuration of 10 g / L thiocarbamide and 20 g / L sodium thiosulfate has surface cracking. In the mixed sulfur salt configuration of thiocarbamide and sodium thiosulfate, the high concentration ratio of sodium thiosulfate to thiocarbamide is not suitable for preparing a crack-free Ni-S coating.

[0099] Comparative Example 6

[0100] This comparative example is to electroplate a Ni-S-P amorphous coating on the surface of an aluminum-silicon alloy (42 wt. % Si). Except for the composition of the electroplating solution, all the preparation processes are the same as those of Example 1. The difference between the electroplating solution of Comparative Example 6 and Example 1 is that the sulfur salt is all replaced by 35 g / L sodium thiosulfate instead of the sulfur salt configuration of 20 g / L thiocarbamide and 15 g / L sodium thiosulfate.

[0101] Figure 11 The surface micro-morphology of the prepared Ni-S-P coating of Comparative Example 6 can be seen from which the Ni-S-P coating prepared by 35 g / L sodium thiosulfate alone has both a convex shape and an irregular shape, and the uniformity of the surface morphology is poor. The high-concentration single sodium thiosulfate sulfur salt is not suitable for preparing a high-quality Ni-S-P coating.

[0102] Comparative Example 7

[0103] This comparative example is to electroplate a Ni-S-P amorphous coating on the surface of an aluminum-silicon alloy (42 wt. % Si). Except for the composition of the electroplating solution, all the preparation processes are the same as those of Example 1. The difference between the electroplating solution of Comparative Example 7 and Example 1 is that the sulfur salt content is lower, and the concentrations of thiocarbamide and sodium thiosulfate are both 5 g / L.

[0104] Figure 12 The surface micro-morphology of the prepared Ni-S-P coating of Comparative Example 7 can be seen from which the surface contains convex shapes with a size of more than 100 μm in diameter, the surface uniformity is poor, and the roughness is high.

[0105] Comparative Example 8

[0106] The present comparative example is the electroplating of a Ni-S-P amorphous coating on the surface of an aluminium-silicon alloy (42 wt.% Si), with the exception of the composition of the plating bath, all the preparation process being identical to that of example 1. The plating bath of comparative example 8 differs from that of example 1 in that the content of sulphur salts is higher: 40 g / L of thiocarbamide and 35 g / L of sodium thiosulphate.

[0107] Figure 13 The surface microtopography of the Ni-S-P coating prepared for comparative example 8 can be seen in the figure, in which the surface appears in the form of exfoliated sheets, between which there are a large number of cracks.

[0108] It should be noted that the above examples are only used to illustrate the present application, and the present application is not limited to the above examples. Those skilled in the art can make appropriate changes within the scope of the claims, and can make several modifications and modifications without departing from the design method of the present application. These should also belong to the protection scope of the present application, and do not affect the essential content of the present application. In the case of no conflict, the features of the embodiments of the present application and the embodiments can be arbitrarily combined and used.

Claims

1. A method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces, characterized in that, Includes the following steps: A constant current power supply is used to electroplate the metal sample, with the metal sample serving as the cathode, to obtain an electroplated nickel-based amorphous polished coating. Electrolytes used in electroplating include nickel salts, sodium thiosulfate, thiourea, phosphate salts, auxiliary salts, buffers, surfactants, and additives. The concentration of sodium thiosulfate in the electrolyte is 10-25 g / L, and the concentration of thiourea is 10-25 g / L.

2. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, The concentration of nickel salt in the electrolyte is 20-100 g / L; And / or, nickel salts include one or more of nickel sulfate or its hydrated salts, nickel chloride or its hydrated salts.

3. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, The concentration of phosphate salts in the electrolyte is 0-50 g / L; And / or, the phosphate salt includes one or more of sodium hypophosphite or its hydrated salt.

4. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, The concentration of auxiliary salt in the electrolyte is 20-40 g / L; And / or, the auxiliary salts include one or more of sodium citrate, ammonium bifluoride, and ammonium sulfate; And / or, the concentration of the buffer in the electrolyte is 20-40 g / L; And / or, the buffer includes one or more of boric acid and citric acid; And / or, the concentration of surfactant in the electrolyte is 0.1-1 g / L; And / or, the surfactant includes one or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfonate, and sodium dodecyl sulfate; And / or, the concentration of the additive in the electrolyte is 0.1-0.6 g / L; And / or, the additives include one or more of saccharin, sodium polydithiopropane sulfonate, coumarin, polyethylene glycol, ytterbium chloride, ytterbium nitrate, and resorcinol.

5. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, The pH of the electrolyte is 3-6.

6. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, Preparation of electrolyte: Dissolve nickel salt, sodium thiosulfate, thiourea, phosphate salt, auxiliary salt, and buffer in pure water respectively. Then, thoroughly mix the nickel salt solution, thiosulfate solution, phosphate salt solution, auxiliary salt solution, and buffer solution in sequence. Add surfactant and additive and mix thoroughly. Finally, adjust the pH value of the solution.

7. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, Electroplating is performed using a constant current pulse output method; And / or, during electroplating, the pulse duty cycle is between 10-70%, the pulse frequency is between 100-50000Hz, and the current density ranges from 0.1-4A / dm³. 2 The water bath temperature of the electrolyte is 20-50℃, the stirring speed of the electrolyte is 10-400rpm, and the electroplating time is 1-12h.

8. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, The materials of the metal samples include one of aluminum, aluminum alloy, silver, gold, steel, nickel, nickel alloy, copper, and copper alloy.

9. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 1, characterized in that, Metal samples undergo pretreatment, alkaline washing, acid washing, and zinc immersion before electroplating.

10. The method for preparing an electroplated nickel-based amorphous polishing coating for ultra-precision machining of metal surfaces according to claim 9, characterized in that, Pretreatment involves grinding, polishing, and ultrasonically cleaning the metal sample with sandpaper to thoroughly remove surface organic matter and oxide layer; And / or, the alkaline washing solution is formulated with the following concentrations: 2-5 g / L NaOH, 40-60 g / L Na2CO3, 40-60 g / L Na3PO4, and 0.5-1 g / L sodium dodecyl sulfate or sodium dodecylbenzene sulfonate. The alkaline washing temperature is 85-90℃, and the alkaline washing time is 5-10 min. And / or, when the material of the metal sample is aluminum and aluminum alloy, the composition of the pickling solution is 5-10 wt.% HNO3, 70-80 g / L NH4HF2, and 10-15 wt.% H2SO4, and the solution is treated at room temperature for 60-80 s. And / or, when the metal sample is made of silver or gold, the pickling solution is 15-20 wt.% HNO3 and 45-60 wt.% HCl, and the sample is treated at room temperature for 3-4 min. And / or, when the material of the metal sample is steel, the pickling solution formula is 150-230 g / L H2SO4 and 250-300 g / L HCl, and the treatment is carried out at 40-50℃ for 20-40 seconds; And / or, when the material of the metal sample is nickel and nickel alloy, the pickling solution formula is 15-20 mL / L H3PO4 and 15-45 mL / L HNO3, and the treatment is carried out at room temperature for 3-4 min; And / or, the zinc immersion solution is formulated with a concentration of 200-300 g / L NaOH, 40-60 g / L ZnO, 1-3 g / L FeCl3, and 5-10 g / L NaKC4H4O6, and is treated at room temperature for 5-10 min.